Plasmids and transposons : environmental effects and maintenance mechanisms - Stuttard, Colin; Rozee, Kenneth R. (Academic Press, 1980)
Plasmids and Transposons: Environmental Effects and Maintenance Mechanisms explores the possibility of the usefulness of plasmids and transposons in controlling pollution. The articles in the book present evolutionary and ecological perspective on the topic. Contributors discussed such topics as aspects of the evolution of composite conjugative plasmids through acquisition of transposons; nosocomial infections; and the importance of plasmid analysis for the appropriate application of epidemiological control measures. Ecologists, environmentalists, physicians, and biologists will find the book.